Mahonia aquifolium Oregon Grapeholly: FPS-375/FP375, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Oregon grapeholly (Mahonia aquifolium), a shrub known for its holly-like leaves, blue fruits, and yellow flowers. It details the plant’s growth habits, including its height, spread, and growth rate, as well as its preferred growing conditions such as light, soil, and water requirements. The document also highlights the plant’s ornamental features, pest resistance, and potential uses in landscaping. Additionally, it mentions various cultivars of Oregon grapeholly, each with unique characteristics. Original publication date October 1999.